Glaucoma among the Malaysian Community - Redhwan Ahmed Al-Naggar; Hisham Alshaikhli; R. R. Al-Rashidi; Bahaa Saleh (The Scientific World Journal)
Background. According to the WHO, glaucoma is the second leading cause of blindness worldwide. About 50% of the world’s glaucoma cases come from the Asian population, and in Malaysia itself, the prevalence of glaucoma is increasing. However, glaucoma is still a foreign word to our community despite the high prevalence. Therefore, there is an urgent need to determine the awareness of glaucoma among the community and its associated factors. Results. This study showed that only 25.2% of our respondents were aware of glaucoma and it is associated with ethnicity, religion, education, and household income. Besides, among those who were aware, they fall into the group of poor knowledge of glaucoma. On the other hand, the knowledge of glaucoma was associated with occupation and the awareness of glaucoma by definition. The validated questionnaire was distributed and the data were analyzed by SPSS software using t-test, one-way ANOVA, and chi-square test. Conclusion. Awareness and knowledge of glaucoma in this population is low. These findings suggest that there is a need for an efficient information and education strategy to be designed and conducted to increase the awareness and knowledge of glaucoma so that early detection can be made and effective management of individuals with this condition can be delivered.